2017
DOI: 10.15587/1729-4061.2017.114367
|View full text |Cite
|
Sign up to set email alerts
|

Tribotechnical research into friction surfaces based on polymeric composite materials

Abstract: Виконано порівняльні дослідження триботехнічних характеристик полімерного композитного матеріалу «Moglice» і розробленого матеріалу ДК-6. Випробування виконувалися на парах тертя «чавун-моглайс» і «чавун-ДК-6». Дослідження необхідні для практичного застосування матеріалів ДК-6 або «Moglice» при відновленні зношених поверхонь тертя. Отримано позитивні результати порівняльних випробувань полімерного композитного матеріалу ДК-6 в порівнянні з «Moglice» Ключові слова: напрямні ковзання верстатів, триботехнічні хар… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…Tribotechnical studies of the polymeric material Moglice indicated positive results and confirmed the characteristics declared by the "Diamant" [10][11][12][13]. However, the use of polymer material Moglice is associated with high financial costs.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Tribotechnical studies of the polymeric material Moglice indicated positive results and confirmed the characteristics declared by the "Diamant" [10][11][12][13]. However, the use of polymer material Moglice is associated with high financial costs.…”
Section: Introductionsupporting
confidence: 61%
“…One example of using composite polymerbased material is the repair of metal-cutting machine slideways worn surfaces using a composite polymer material Moglice (Diamant) [11][12][13]. Moglice is a two-component, coldcuring antifriction polymeric material used to rebuild and restore all types of sliding surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Ударопрочность (impact strength) эпоксидов вырастала примерно на 20 % после введения SiC, а введение резин усиливало эффект до 1.5-2-кратного роста прочности. Авторы [7][8][9] считают, что на сегодня исследований по системам эпоксид+SiC недостаточно.…”
Section: литературный обзорunclassified
“…Авторы Между тем, подобные композиты давно и с успехом применяются под различными коммерческими марками -в частности от немецких фирм [8,9]. Ввиду их высокой дороговизны, научное изучение таких систем с последующим созданием уде-…”
Section: литературный обзорunclassified
“…However, the cited studies did not consider a technique for using composite materials under conditions of cavitation destruction. Advancements on the cavitation-corrosion wear [5,6] consider the use of metallic coatings at the level of nanomaterials, as well as the application as the base for stainless steel materials. It should be noted, however, that the cost of such strengthening makes the cited studies impractical for use under conditions of pumping equipment.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%